Finding faith : the spiritual quest of the post-boomer generation - Flory, Richard W.; Miller, Donald E. (Donald Earl), 1946- (Rutgers University Press, 2008)
Despite the masses still lining up to enter mega-churches with warehouse-like architecture, casually dressed clergy, and pop Christian music, the?Post-Boomer? generation?those ranging in age from twenty to forty?is having second thoughts. In this perceptive look at the evolving face of Christianity in contemporary culture, sociologists Richard Flory and Donald E. Miller argue that we are on the verge of another potential revolution in how Christians worship and associate with one another. Just as the formative experiences of Baby Boomers were colored by such things as the war in Vietnam, the.